2011
DOI: 10.1143/jpsj.80.113706
|View full text |Cite
|
Sign up to set email alerts
|

Subgap in the Edge States of Two-Dimensional Chiral Superconductor with Rough Surface

Abstract: We discuss the rough surface effects on a two-dimensional chiral kx + iky superconductor. The atomic scale roughness at the surface is considered using the random S matrix model. The roughness effects on the self-consistent order parameter, the surface mass current and the surface density of states are studied using the quasi-classical theory. We find that the surface mass current is suppressed by the surface roughness. The surface density of states shows a quite similar behavior to that of superfluid 3 He B p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Á B . Recently, Nagato et al 306) elucidated the physical origin of the subgap Á Ã which is a consequence of the level repulsion between the bound states and scattering states. The two different energy scales, Á Ã and Á B , were observed as a kink and peak in the complex impedance ZðTÞ.…”
Section: Observations Of Surface Bound States In 3 He-bmentioning
confidence: 99%
“…Á B . Recently, Nagato et al 306) elucidated the physical origin of the subgap Á Ã which is a consequence of the level repulsion between the bound states and scattering states. The two different energy scales, Á Ã and Á B , were observed as a kink and peak in the complex impedance ZðTÞ.…”
Section: Observations Of Surface Bound States In 3 He-bmentioning
confidence: 99%
“…There have been numerous works on the effect of surface roughness that causes diffusive scattering of quasiparticles [145,146,147,148,149,150,151,152,153]. The surface roughness drastically changes the surface structure of order parameters and low-lying surface states in the superfluid 3 He-B [106,108,152,154]. The pair-breaking effect and the enhancement of the surface density of states due to the existence of the surface Andreev bound states have been observed in several experiments [109,110,271,112,113,114,115,116,117,118,155,156,157,158,159].…”
Section: 3mentioning
confidence: 99%
“…Despite the fact that previous studies revealed important aspects of these phenomena [84][85][86], there is still a need for systematic study and quantitative predictions. The purpose of this study is to evaluate the influence of the degree of diffusive electron scattering at interfaces in p-wave superconductors on the DoS.…”
Section: Introductionmentioning
confidence: 99%